2013
DOI: 10.1021/ja3091615
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Molecules as Nanomotors

Abstract: Using fluorescence correlation spectroscopy, we show that the diffusive movements of catalase enzyme molecules increase in the presence of the substrate, hydrogen peroxide, in a concentration-dependent manner. Employing a microfluidic device to generate a substrate concentration gradient, we show that both catalase and urease enzyme molecules spread toward areas of higher substrate concentration, a form of chemotaxis at the molecular scale. Using glucose oxidase and glucose to generate a hydrogen peroxide grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
405
4
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(435 citation statements)
references
References 47 publications
23
405
4
3
Order By: Relevance
“…Sen and coworkers (39,40) have shown that catalytically active enzymes have larger diffusion coefficients than their inactive counterparts in the absence of substrate. Recently, chemotaxislike drift of enzymes in the presence of substrate gradients has been observed and used for sorting of the enzymes (41).…”
Section: Discussionmentioning
confidence: 99%
“…Sen and coworkers (39,40) have shown that catalytically active enzymes have larger diffusion coefficients than their inactive counterparts in the absence of substrate. Recently, chemotaxislike drift of enzymes in the presence of substrate gradients has been observed and used for sorting of the enzymes (41).…”
Section: Discussionmentioning
confidence: 99%
“…While the results of Fukushima and coworkers [91] may seem surprising, recent work indicating an ability of low-entropy sunlight to impart long-range order in bulk as well as surface water [92] provides a plausible route by which water CD's may provide energy catalyzing chemical reactions not only at enzymes but indeed near many hydrophobic or hydrophilic surfaces [93,94], as well as for actual diffusion of enzymes through bulk aqueous solution toward areas of high local substrate concentration [95][96][97].…”
Section: Interaction With Electric and Magnetic Fieldsmentioning
confidence: 99%
“…Bacteria and other single-or multi-cellular organisms propel themselves up or down the concentration gradient of a particular substance in their search for nutrients or to avoid antagonists. Inspired by chemotaxis in biology, researchers synthesized artificial microswimmers [2,3] that can move in response to a chemical stimulus [4,5]. They showed that Janus particles (JP), in the form of two-faced Au-Pt colloidal rods that catalyze hydrogen peroxide redox, are attracted by a hydrogen peroxide source.…”
Section: Introductionmentioning
confidence: 99%